Inhibition of IL‐17A by secukinumab shows no evidence of increased Mycobacterium tuberculosis infections. Issue 8 (25th August 2017) - Kammüller, Michael; Tsai, Tsen‐Fang; Griffiths, Christopher EM; Kapoor, Nidhi; Kolattukudy, Pappachan E; Brees, Dominique; Chibout, Salah‐Dine; Safi, Jorge; Fox, Todd
Abstract : Secukinumab, a fully human monoclonal antibody that selectively neutralizes interleukin‐17A (IL‐17A), has been shown to have significant efficacy in the treatment of moderate to severe psoriasis, psoriatic arthritis and ankylosing spondylitis. Blocking critical mediators of immunity may carry a risk of increased opportunistic infections. Here we present clinical and in vitro findings examining the effect of secukinumab on Mycobacterium tuberculosis infection. We re‐assessed the effect of secukinumab on the incidence of acute tuberculosis (TB) and reactivation of latent TB infection (LTBI) in pooled safety data from five randomized, double‐blind, placebo‐controlled, phase 3 clinical trials in subjects with moderate to severe plaque psoriasis. No cases of TB were observed after 1 year. Importantly, in subjects with a history of pulmonary TB (but negative for interferon‐γ release and receiving no anti‐TB medication) or positive for latent TB (screened by interferon‐γ release assay and receiving anti‐TB medication), no cases of active TB were reported. Moreover, an in vitro study examined the effect of the anti‐tumor necrosis factor‐α (TNFα) antibody adalimumab and secukinumab on dormant M. tuberculosis H37Rv in a novel human three‐dimensional microgranuloma model. Auramine‐O, Nile red staining and rifampicin resistance of M. tuberculosis were measured. In vitro, anti‐TNFα treatment showed increased staining for Auramine‐O, decreased Nile red staining and decreased rifampicin resistance, indicative of mycobacterial reactivation. In contrast, secukinumab treatment was comparable to control indicating a lack of effect on M. tuberculosis dormancy. To date, clinical and preclinical investigations with secukinumab found no evidence of increased M. tuberculosis infections. Tuberculosis: An anti‐inflammatory drug does not reawaken infection: Immunosuppressive drugs have the potential to reactivate opportunistic infections, such as Mycobacterium tuberculosis . Some studies indicate that interleukin‐17¦A (IL‐17¦A) may help control such infections. Researchers led by Michael Kammüller at the Novartis Institutes for Biomedical Research in Basel, Switzerland, examined whether secukinumab, an anti‐inflammatory drug that inhibits IL‐17¦A, for treating inflammatory diseases such as psoriasis, can reactivate latent tuberculosis. An investigation of 132 patients with a history of tuberculosis who had received secukinumab revealed no cause for concern for mycobacterial reactivation. Furthermore, in contrast to a tumor necrosis factor inhibiting immunosuppressive drug (adalimumab), secukinumab did not reactivate infection in an experimental model of latent tuberculosis in human white blood cells. These findings indicate that secukinumab does not put psoriasis patients at greater risk of reactivating mycobacterial infection.